PENGARUH KUALITAS PELAYANAN, PERSEPSI HARGA, DAN FASILITAS TERHADAP KEPUASAN KONSUMEN PADA D’COFFEE CUP PRAPEN SURABAYA - Adelia Eka Putri; Sumiati Sumiati (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This research aims to test and analyze the influence of Service Quality, Price Perception and Facilities on Consumer Satisfaction. The population used in this research were all consumers at the D'coffee Cup Prapen cafe in Surabaya using a sampling technique, namely non-probability sampling, of 100 samples based on specified criteria. This research data was analyzed using multiple linear regression analysis and F Test using the SPSS Version 30 analysis tool. The method used in this research is a quantitative research method. This research involves collecting data through questionnaires distributed to respondents. This research design is based on the philosophy of positivism and aims to test the hypotheses that have been established. Samples were taken using the Lemeshow formula because the population was not known for certain. The research results show that 1) Service quality has a significant effect on consumer satisfaction, 2) Price perception has a significant effect on consumer satisfaction, 3) Facilities have a significant effect on consumer satisfaction, 4) Service quality, price perception and facilities together have a significant effect on consumer satisfaction. The overall research results provide implications for D'coffee Cup cafe owners to carry out evaluations or plans to maximize consumer satisfaction. High quality service, coupled with affordable prices and adequate facilities, will make consumers feel satisfied, comfortable, and able to enjoy products in a relaxed manner.